Nepal in a Triangular Geopolitical Rivalry - Lamsal, Yuba Nath (NCWA Annual Journal, 2025)
The global power structure continues to change which is a general phenomenon of history. These changes are marked by some phenomenal shifts in the international order. Wars shaped the world order and marked the shift of political power from one country to another and from one region to another. Europe at one point was the master and pivot of world power and politics, while the Europe-centric international power shifted to America after World War II with the United States dictating and the rest of the world taking notes. The Soviet Union, too, emerged as one of the superpowers but it could not sustain its prowess for a long time and collapsed in the early 1990s giving rise to a unipolar world order led by the United States. However, this international order too is in the process of change but it is not yet certain what shape the new world order will exactly take. However, it is certain that the Atlantic centric world order and power will not last long and the international power will shift to Asia to make the Asian century a reality in which China and India will be the key actors. This article examines how Nepal, situated in a crucial location between the two rival powers of Asia along with an increasing role of the US in the region, should use diplomatic acumen to face the challenges in maintaining a balance in its relations with great powers.